Evaluation of the 177mLu-concentration in in-house produced 177Lu-radiopharmaceuticals and commercially available Lutathera® - Matthias Balzer; Fleur Spiecker; Stephanie Bluemel; Holger Amthauer; Winfried Brenner; Sarah Spreckelmeyer (SpringerOpen, 2023)
Abstract Background 177Lu-radiopharmaceuticals can contain the metastable impurity [177mLu]lutetium with a physical half-life of 160.4 days, in varying concentrations depending on the route of production of the radionuclidic precursor [177Lu]lutetium. Due to the long half-life of [177mLu]lutetium, difficulties with waste disposal or sterility testing could arise. Here, we analyzed several 177Lu-samples of different origins and suppliers regarding their 177mLu-concentration. Results All samples tested showed a 177mLu-concentration in the range that was stated on the certificate of analysis from the supplier which is in accordance with the European Pharmacopoeia. Conclusions Although all 177mLu-concentrations were in accordance with the European Pharmacopoeia, we need to take into account the respective national legislation regarding radioactivity release limits. With regard to the German legislation, several probes for sterility testing in external laboratories could not be released for transport due to the concentration of [177mLu]lutetium. Moreover, waste water tanks should specifically be monitored for 177mLu-concentration, when e.g. Lutathera® is administered in the clinic.